Endocrine Emergency and Urgency Defined - Sanjay Kalra; Shinjan Patra; Parth Jethwani; Nitin Kapoor (Journal of the Pakistan Medical Association, 2025)
Endocrine emergencies traditionally focus on life-threatening conditions like diabetic ketoacidosis, thyroid storm, adrenal crisis, or severe hypoglycaemia. However,less recognised endocrine conditions also demand immediate attention due to their potential to disrupt the quality of life and result in downstream complications if not timely intervened. This perspective explores unconventional endocrine emergencies such as short stature, pituitary adenomas, infertility, polycystic ovary syndrome, diabetes and hypothyroidism in pregnancy, and low bone mass and osteoporosis. We propose a broader definition of endocrine emergencies, encompassing biomedical, psychological, and social dimensions to ensure person-centred care. Prompt intervention in these endocrine emergencies is essential to mitigate immediate risks, prevent long-term physical and psychological damage, and significantly improve quality of life, highlighting the critical need for swift action in these situations. Keywords: Endocrine emergency; Endocrine urgency; Psychological distress; Person-centred care; Quality of life.